Globally optimising open-pit and underground mining operations under geological uncertainty. (2nd January 2016) - Montiel, L.; Dimitrakopoulos, R.; Kawahata, K.
Abstract : A mining complex may be comprised of multiple components, including open-pit and underground operations. Traditional approaches in mine planning do not account for the various components simultaneously leading to under-value solutions. Over the last decade, some methods have been developed to incorporate multiple components of the mining value chain during optimisation. Even though these new methods incorporate more decisions and flexibility to the optimisation of a mining complex, they may either ignore uncertainties associated with the mining project or consider decisions taken before optimisation. This paper presents a method that optimises mining complexes comprised of multiple open-pits, underground operations and processing destinations. Mining, blending, processing and transportation decision variables are simultaneously optimised while accounting for geological uncertainty. The method uses a simulated annealing algorithm at different decision levels in order to generate a stochastic-based extraction sequence and processing policies. A case study shows its ability to generate a higher NPV while facing a reduced amount of risk when compared to traditional optimisation methods.